Konstruksi Ilmu Keislaman: Ontologi, Epistemologi, Dan Aksiologi Dalam Menggagas Format Pendidikan Nondikotomik Antara Pendidikan Agama Dan Pendidikan Umum - Suhaimis; Amrizon; Julhadi (Universitas Majalengka, 2024)
This research aims to explore the construction of Islamic science through the study of ontology, epistemology, and axiology, as well as develop educational formats that are not dichotomized between religious education and general education. A qualitative approach is used in this study, with descriptive and interpretive analysis methods on classical and contemporary Islamic literature. The results of the study show that from the perspective of Islamic ontology, all aspects of life are an inseparable unit, including religious science and general science. Epistemologically, Islam emphasizes the integration between revelation and reason in the process of seeking knowledge. From the axiology side, knowledge must be directed to the benefit of the people and the welfare of humanity as a whole. This study proposes a non-dichotomous education model that integrates Islamic values with general science. This model is expected to be able to produce graduates who not only have high academic competence, but also have a strong moral and spiritual foundation. Thus, Islamic education can play a more effective role in shaping individuals with a complete personality and contributing positively to society.